Compartimos nuestras costumbres navideñas - Requejo Quijano, Angelica Magdalena (2020)
The session entitled: “We share our Christmas customs”, was developed in the area of Social Personnel, taking into account the competition Lives and participates democratically in the search for the common good. The ability to interact with all people has been considered. In this learning session it has been possible to achieve performance. Perform daily activities with your classmates such as greeting them and is interested in knowing their customs at Christmas, as well as the places from which they come._x000D_ Within the thematic body, documents related to the customs of children in their families during Christmas, active and respectful listening, as well as the common good and democratic participation have been considered. For the preparation and execution of the learning session, pedagogical processes such as motivation and exploration of previous knowledge, problematization, purpose and organization, management and accompaniment of learning, and evaluation have been taken into account. In addition, the problematization, analysis of the information and the agreement or decision making, as didactic processes of the Social Personnel area.